2014
DOI: 10.1590/rou.2014.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorhexidine gluconate on porosity and compressive strength of a glass ionomer cement

Abstract: ResumoIntrodução: Por apresentar ampla atividade antibacteriana, a clorexidina (CHX) tem sido amplamente utilizada em odontologia, podendo ser facilmente incorporada ao cimento de ionômero de vidro (CIV) e liberada consequentemente na cavidade bucal. Objetivo: O objetivo neste estudo foi avaliar a porosidade e resistência à compressão de um CIV, ao qual foi adicionado diferentes concentrações de CHX. Material e método: Os espécimes foram preparados com CIV (Ketac Molar Esaymix) e divididos em 4 grupos de acord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…3 . Such findings are in accordance with Farret et al [ 46 ], Marti et al [ 47 ], and Jaidka et al [ 32 ], who stated that incorporation of antimicrobial agents at certain concentrations did not affect the compressive strength properties of GIC.…”
Section: Discussionsupporting
confidence: 92%
“…3 . Such findings are in accordance with Farret et al [ 46 ], Marti et al [ 47 ], and Jaidka et al [ 32 ], who stated that incorporation of antimicrobial agents at certain concentrations did not affect the compressive strength properties of GIC.…”
Section: Discussionsupporting
confidence: 92%
“…A study by El Tatar showed that SPE combined with GIC at a concentration of 1% SPE maintained the same level of compressive strength as that of the control group [ 20 ], and this is consistent with the present study, where a lower concentration of the extract, i.e., Group I (2:1:1), unaltered the compressive strength. Farret et al [ 24 ], Pavithra et al [ 25 ], and Marti et al [ 26 ] also noted similar results, indicating that the addition of antimicrobial agents at particular concentrations had no impact on the compressive strength characteristics of GIC.…”
Section: Discussionmentioning
confidence: 71%